Why was apparent evidence ignored? The delayed relaxation of China's birth control. Issue 2 (20th February 2020) - Jing, Yijia; Hu, Zhan
Abstract: The ideal of evidence‐based policy making (EBPM) may be hindered by delayed policy response to disclosed evidence. This article adopts Allison's three‐lens decision‐making framework to highlight technical, organizational, and political causes of delayed policy responses to apparent evidence. The study uses China's birth control policy as a case to examine the lag of policy adjustments. Although ample supply of evidence suggested earlier relaxation of China's one‐child policy, major adjustments only happened after 2013 and failed to achieve significant results. The study indicates that a politics‐informed EBPM approach may better position the role of evidence in policy processes by taking into consideration the unavoidable influences of institutions and politics. Abstract : This article adopts Allison's three‐lens decision‐making framework to highlight technical, organizational, and political causes of delayed policy responses to apparent evidence. The study uses China's birth control policy as a case to examine the lag of policy adjustments and indicates the need to have a politics‐informed EBPM approach.